Reduction of polycyclic aromatic hydrocarbons promoted by cobalt or manganese nanoparticles - Nador, Fabiana Gabriela (2010)
A new methodology for the partial reduction of polycyclic aromatic and heteroaromatic hydrocarbons under mild reaction conditions is presented, the process being a reasonable alternative to the catalytic hydrogenation or the Birch reaction. The reduction protocol described is based on the use of cobalt or manganese nanoparticles generated in situ in a simple and economic way, by reduction of commercially available CoCl2·6H2O or MnCl2·2H2O in the presence of lithium sand and the corresponding PAH, acting itself as an electron carrier. The use of a deuterium-oxide-containing cobalt(II) salt allows the simple preparation of deuterium labeled products. The regiochemistry and degree of reduction in the case of 1-substituted naphthalene derivatives markedly depends on the nature of the metal-NPs used. © 2010 Elsevier Ltd. All rights reserved.